2001
DOI: 10.1046/j.1460-9592.2001.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Comparison of the Safety and Effectiveness of Placement of Endocardial Pacemaker and Defibrillator Leads Using the Extrathoracic Subclavian Vein Guided by Contrast Venography Versus the Cephalic Approach

Abstract: The purpose of this prospective randomized study was to compare the safety and efficacy of the cephalic approach versus a contrast-guided extrathoracic approach for placement of endocardial leads. Despite an increased incidence of lead fracture, the intrathoracic subclavian approach remains the dominant approach for placement of pacemaker and implantable defibrillator leads. Although this complication can be prevented by lead placement in the cephalic vein or by lead placement in the extrathoracic subclavian o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
100
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 0 publications
3
100
1
Order By: Relevance
“…It is remarkable that early symptomatic venous obstruction is clinically rarely Venous obstruction after ICD recognized. A recent prospective study, which followed 200 patients for a mean of 540 days after device implantation reported only two patients with clinically recognized acute subclavian vein thrombosis [18].…”
Section: Previous Reports In Pacemaker Patientsmentioning
confidence: 99%
“…It is remarkable that early symptomatic venous obstruction is clinically rarely Venous obstruction after ICD recognized. A recent prospective study, which followed 200 patients for a mean of 540 days after device implantation reported only two patients with clinically recognized acute subclavian vein thrombosis [18].…”
Section: Previous Reports In Pacemaker Patientsmentioning
confidence: 99%
“…Furthermore, axillary vein has been demonstrated to be an effective method with less acute complications and less lead failures in the longer term compared with subclavian access, especially for PM implantation [10][11][12][13][14][15][16][17][18][19]. However, data on axillary vein approach for ICD implantation are limited.…”
Section: Introductionmentioning
confidence: 99%
“…5 This method is relatively safe, effective and has the additional benefit of documenting the patency of the venous system. However, problems occur in relation to contrast and the possibility of pneumothorax because of unknown vessel depth.…”
Section: Kim Kh Et Almentioning
confidence: 99%